قاعدة المعدول به عن سنن القياس فغيره عليه لا يقاس :‏ ‏دراسة أصولية تطبيقية /‏ - سوزائي، فاروق سلامي (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2011)
This research focuses on the study of “The Maxim of the Non-extendibility of Exceptional Cases from the Principle of Qiyās (Analogy) to Other Cases.” This has been performed by explaining the definition of this maxim, discussing the opinions of jurists and Usūlī Scholars on this issue, identifying the point of dispute in this regard and solving it, explaining whether it is lawful or not to extend the rulings of cases that are exceptional from the principle of analogy to other cases by analogy, and highlighting what is preferable view in this regard. It also strives to find the relationship of these exceptional cases from the principle of Qiyās with rukhsah, particularization of the effective cause (takhsis al-illah), juristic preference (al-istihsān), public interest and custom. The research also focuses on discussing opinions of jurists and Usūlī scholars on some classical juristic issues with their contemporary applications along with their relationship with the maxim mentioned above. The study is based on inductive, descriptive, analogical and comparative methods to deal with the theoretical and applied aspects simultaneously. This study has achieved some important findings. Among them: the majority of 'ulamā'(scholars) consensually agreed upon the existence of the rulings that are exceptional from the principle of analogy and general maxims of Islamic Sharī'ah. They classify them into four main categories: the rulings that are specific for particular cases where the meaning of specification is not understandable; the rulings that are originally not understandable; the rulings that are understandable, but they have no counter cases which could be analogized upon them; and the rulings that are excepted from general maxims, the meaning of this exception is understandable, and they have counter cases. The study showed that the majority of Usūlī Scholars agree not to make analogy in the first three categories, but they do not agree upon the fourth category which has led to some disputations among them. On the other hand, Ibn Taymiyyah and Ibn al-Qayyim refuse the phrase: “Exceptional Cases from the Principle of Analogy or Cases Contrary to Analogy” to be used in Islamic Sharī'ah. Regarding majority scholars' disputation on the fourth category, the researcher preferred permission of analogy upon the ruling that is exceptional from the principle of analogy, if it is understandable and if it has a counterpart to participate in its meaning. As for disagreement with Ibn Taymiyyah and Ibn al-Qayyim it was found that the difference between them is in words, not in the meaning; and all of them support using this maxim with the reservation of Ibn Taymiyyah and his student in using it without any restriction. Furthermore, in the last chapter the researcher found out that unintentional eating or drinking by fasting person and also the advance purchase (Al-salam) have been legislated contrary to analogy and excepted from general maxims of the Sharī'ah. In contrast, the leasing (Al-ijārah) and business of partnership (Al-mudārabah) have been legislated in accordance with the analogy and general maxims of Islamic Sharī'ah.